The assessment of water quality in two main rivers in Kuantan, Pahang - Zainutdin, Fatin Khairunnisa; Mat Yusof, Afzan (IIUM Press, International Islamic University Malaysia, 2017)
Despite the enforcement of Environmental Quality Act in 1974, water quality of rivers in Malaysia is still deteriorating. Information collected regarding water quality in rivers especially in the state of Pahang is still insufficient. Therefore, the objectives of this study were to detect the occurrence of Cryptosporidium oocysts and to assess the physico-chemical and heavy metal parameters in Kuantan River and Balok River. Six water samples were collected from Kuantan River and Balok River. Water samples were filtered followed by the purification of Cryptosporidium oocyst using the immunomagnetic separation technique and stained by fluorescein isothiocyanate–staining. Physical parameters were measured directly at the sampling locations using the handheld multi-parameter instrument while the assessment of chemical and heavy metal were done in the laboratory. Results obtained were then compared with the Interim National Water Quality Standards (INWQS) which is the standard parameters used to assess the water quality in surface water in Malaysia. Kuantan River and Balok River were contaminated with Cryptosporidium oocysts and chemical contaminants. However, water quality in both Kuantan River and Balok River varies depending on the sampling points. Cryptosporidium oocysts were detected in all water samples. With regards to INWQS, our results reported a lower level of dissolved oxygen (<5 mg/L) and elevated level of chemical oxygen demand (>50 mg/L), biological oxygen demand (>4 mg/L), nitrite (>1 mg/L) and chloride (>200 mg/L) at certain sampling locations. Of 23 elements measured, only 9 elements were detected (aluminium, boron, calcium, cobalt, iron, potassium, magnesium, sodium and strontium). The presence of heavy metals; aluminium (>0.5 mg/L) and iron (>0.8 mg/L) at several locations were beyond the INWQS safety limit range. Results obtained from this study will be very useful for future river management. Further studies on molecular characterization of Cryptosporidium species in river is highly recommended. Besides that, more parameters can be added in the future for more extensive information. It is hoped that this study can provide new data to the growing body of literature on the presence of Cryptosporidium oocyst as well as the physico-chemical assessment in Kuantan River and Balok River.